The Design Of Web-Based Service Satisfaction Assessment At The Department Of Industry And Trade Of Bengkulu Province - Rahmi Hidayat; Asnawati Asnawati; Aji Sudarsono (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
In an effort to improve the services quality, facilities and infrastructure are needed that support the process of providing services. Where there needs to be proper treatment starting from the input, process, to the output of the services provided. Good relations and communication with the community are needed in an effort to maintain the continuity of a continuous service process. In addition, a service process environment is needed that is able to provide comfort and convenience for the community. The web-based service satisfaction assessment application at the Department of Industry and Trade of Bengkulu Province is an application built to facilitate the community in providing value to the services provided by officers which aims to evaluate the satisfaction assessment provided by the community. This application has applied the Servqual Method where the assessment is divided into 2 parts, namely perceptions and expectations. The web-based service satisfaction assessment application at at the Department of Industry and Trade of Bengkulu Province was made using the PHP programming language and MySQL database. This application can be accessed online via the link http://rahmi.vad.my.id/, so that people can fill out the assessment anywhere and anytime. The web-based service satisfaction assessment application at at the Department of Industry and Trade of Bengkulu Province is divided into 2 access rights, namely Administrator and Community. Based on the tests that have been carried out, the results show that the functionality of the web-based service satisfaction assessment application at the Department of Industry and Trade of Bengkulu Province runs as expected.